PEMANFAATAN LIMBAH RUMAH TANGGA SEBAGAI BAHAN DASAR PUPUK ORGANIK UNTUK MENANGGULANGI MASALAH SAMPAH DAN MENGURANGI KETERGANTUNGAN PETANI PADA PUPUK KIMIA DI DESA GUNJAN ASRI KECAMATAN BAYAN KABUPATEN LOMBOK UTARA - Thoriq, Aqmal; Anita, Anita; Maulana, Irvan; Jumriati, Jumriati; S, Rosmarina; Maghfira, Laila; Firdaus, Muhammad Fawaris; Nagib, Muhammad; Nurida, Nurida; Sulhianita, Sulhianita (Jurnal Wicara, 2023)
Gunjan Asri Village is one of 12 villages in Bayan District, North Lombok Regency with an area of 2,019 Ha. The population in 2022 of 2,754 people is the majority of farmers. The agricultural potential in Gunjan Asri is quite large, but this potential has not been utilized optimally, marked by sub-optimal crop yields due to the high cost of chemical fertilizers. Therefore, one of the efforts to reduce farmers' dependence on the use of chemical fertilizers in increasing agricultural production is the use of organic fertilizers made from household waste. Utilization of household waste for organic fertilizer also aims to educate the public in creating sanitation and a healthy environment. The result of this organic fertilizer product is an invention that still needs to be studied and tested through further research so that it can be marketed.